The acute toxic effects of 1-alkyl-3-methylimidazolium nitrate ionic liquids on Chlorella vulgaris and Daphnia magna - Zhang, Cheng; Zhang, Shuai; Zhu, Lusheng; Wang, Jinhua; Wang, Jun; Zhou, Tongtong (Environmental pollution (1987), 2017)
Given their increasingly widespread application, the toxic effects of ionic liquids (ILs) have become the subject of significant attention in recent years. Therefore, the present study assessed the acute toxic effects of 1-alkyl-3-methylimidazolium nitrate ([Cnmim]NO3 (n = 2, 4, 6, 8, 10, 12)) on Chlorella vulgaris and Daphnia magna. The sensitivity of the tested organism Daphnia magna and the investigated IL concentrations in water using high-performance liquid chromatography (HPLC) were also evaluated to demonstrate the reliability of the present study. The results illustrated that Daphnia magna is indeed sensitive to the reference toxicant and the investigated ILs were stable in the aquatic environment. The 50% effect concentration (EC50) was used to represent the acute toxic effects on Chlorella vulgaris and Daphnia magna. With the increasing alkyl-chain lengths, the toxicity of the investigated ILs increased in both the test organisms. Accordingly, the alkyl-chain lengths can cause significantly toxic effects on aquatic organisms, and Daphnia magna are much more sensitive than Chlorella vulgaris to the imidazolium-based ILs used in the present study. Furthermore, the present study provides more information on the acute toxic effects of 1-alkyl-3-methylimidazolium nitrate. [Display omitted] •The Daphnia magna are more sensitive than Chlorella vulgaris to the ILs [Cnmim]NO3.•The alkyl-chain lengths can cause notably toxicity to the tested aquatic organisms.•The doses of the tested ILs are at a relatively stable level in the present study. Alkyl-chain lengths have significant toxic effects on aquatic organisms, and the doses of the tested ILs are at a relatively stable level in the present study.